Entrapment of the lateral cutaneous nerve of the calf. (2nd July 2013) - Khalil, Nofal M; Nicotra, Alessia; Kaplan, Charles; O'Neill, Kevin S
Abstract : Isolated lesion of lateral cutaneous nerve of the calf (LCNC), particularly due to entrapment, is rarely reported in the literature. Patients usually present with sensory symptoms in the lateral aspect of the calf. Treatment is usually by local applications or local steroid/anaesthetic injection. We report the first case of LCNC entrapment in a 35-year-old man which is documented by nerve conduction studies. The patient had a temporary improvement following a local anaesthetic/steroid injection. Owing to the recurrence of symptoms, the patient opted for surgery. About 1 year after surgery, the symptoms disappeared completely.